Export Orientation of Service Companies on the Increase - Alexander Eickelpasch (Weekly Report, 2008)
In the course of increasing internationalisation of the German economy, growth in export can also be expected for the German service sector. However, there has only been limited information about the export behaviour of German service companies so far. This gap can be closed to some extent by statistics existing since 2000. This study confirms that export orientation increased between 2000 and 2005. The proportion of exporting companies has augmented as well as the share of exports in turnover. There are differences according to industrial sectors. Small companies are generally less export-oriented than larger ones. The export potential is assessed as being favourable. One reason is that modern communication technologies ease the international exchange of information. The other reason is that in the international market-both in the European Union and in other countries-demand for services will also grow with investment by German companies abroad.
Keywords: F14; F23; L80; 330; export; service sector; small and medium-sized enterprises